Sox15 Methylation Inhibits Cell Proliferation Through Wnt Signaling in Hepatocellular Carcinoma - Wei, Bajin; Chen, Hao; Chen, Xiaobin; Guo, Danjing; Hong, Liangjie; Zheng, Shusen (Frontiers in Oncology, 2022)
The expression of the SRY-Box Transcription Factor 15 (Sox15) is reduced by DNA methylation, and its progression is suppressed within numerous tumors. However, its effect on hepatocellular carcinoma (HCC) remains unknown. In the present work, the clinical importance and function of Sox15, as well as the underlying molecular mechanism, were explored within HCC. The expression of Sox15 is reduced and positively correlated with prognosis in HCC as analyzed by GEPIA (Gene Expression Profiling Interactive Analysis) and OncoLnc. Meanwhile, the hypermethylated Sox15 promoter CpG-site predicted a dismal HCC prognosis. Besides, ectopic Sox15 expression within the HCC cells (LM3, HUH7, SK-hep-1) remarkably inhibited in vitro cell growth and inhibited xenograft tumorigenesis in the nude mice. Moreover, Sox15 inactivated the Wnt pathway under both in vivo and in vitro conditions. To summarize, Sox15 played a tumor suppressor role within the HCC via the inactivated Wnt pathway. Sox15 and CpG-site methylation of its promoter are the factors that independently predict the prognosis of HCC.